2003
DOI: 10.1002/art.11260
|View full text |Cite
|
Sign up to set email alerts
|

Coronary artery angiography in systemic lupus erythematosus patients with abnormal myocardial perfusion scintigraphy

Abstract: Objective. According to published studies, 16-82% of systemic lupus erythematosus (SLE) patients have abnormal findings on myocardial perfusion tests, but it has not been established whether these patients also have abnormal findings on coronary angiography. The aim of this study was to evaluate the frequency of abnormal findings on coronary angiography in SLE patients in whom myocardial perfusion scintigraphy revealed abnormalities.Methods. Ninety female SLE patients (ages 20-55 years, disease duration >5 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
15
0
3

Year Published

2005
2005
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 43 publications
3
15
0
3
Order By: Relevance
“…Accelerated atherosclerosis is considered an important cause of morbidity and mortality in patients with SLE [16] and highlights the importance of recognizing and controlling modifiable risk factors [17]. …”
Section: Discussionmentioning
confidence: 99%
“…Accelerated atherosclerosis is considered an important cause of morbidity and mortality in patients with SLE [16] and highlights the importance of recognizing and controlling modifiable risk factors [17]. …”
Section: Discussionmentioning
confidence: 99%
“…HT is a well recognised risk factor for CV disease development in SLE patients (Petri, PerezGutthann et al 1992) as evidenced by several studies reporting its contribution in plaque formation (IMT measurement, coronary angiography) and arterial stiffening (Sella, Sato et al 2003;Selzer, Sutton-Tyrrell et al 2004;Maksimowicz-McKinnon, Magder et al 2006;Cypiene, Dadoniene et al 2010;Gallelli, Burdick et al 2010). Several studies so far have confirmed the increased prevalence of arterial HT in these patients, ranging from 33% to 56% (de Leeuw, Freire et al 2006;Bellomio, Spindler et al 2009;Duarte, Couto et al 2009;Boucelma, Haddoum et al 2011;Sabio, Vargas-Hitos et al 2011).…”
Section: Slementioning
confidence: 99%
“…Mittels Stress-Myocardszintigraphie wurden Perfusionsdefekte bei 23-40% der untersuchten SLE-Patientinnen ohne Angina pectoris nachgewiesen [4, 16,37]. Bei 8 von 21 Frauen (38%) mit Perfusionsausfällen konnte koronarangiographisch eine KHK bestätigt werden.…”
Section: Considering Systemic Lupus Erythematosus As Example For Acceunclassified
“…Bei 8 von 21 Frauen (38%) mit Perfusionsausfällen konnte koronarangiographisch eine KHK bestätigt werden. Bei diesen Patientinnen fanden sich signifikant mehr traditionelle Risikofaktoren (insbesondere arterielle Hypertonie), Frauen mit mindestens 4 Risikofaktoren hatten in 67% bereits Koronarstenosen [37].…”
Section: Considering Systemic Lupus Erythematosus As Example For Acceunclassified